IMPROVING LISTING SKILLS THROUGH AUDIOVISUAL LEARNING MODELS IN CLASS X MA STUDENTS AT MIZANUL ULUM SANROBONE - Reski Reski; Sitti Rabiah; Andi Puspitasari (Citra Dharma Cindekia, 2022)
The purpose of this study was to describe the process of learning to develop listening skills by using an audiovisual learning model in class X MA Islamic Boarding School Mizanul Ulum Sanrabone. The research subjects were students of class X with a total of 12 people, the type of research used was class action research. Classroom action research was carried out in 2 cycles, in which each cycle consisted of 4 stages, namely planning, implementing action, observing and reflecting. The research results that have been described are information on student learning outcomes that have been carried out in each cycle. In this discussion, it is described using learning listening skills using audiovisual media, so the results of the research mean that the average score for increasing pre-cycle news listening skills is 61, an increase of 30 points. And the average value of cycle 1 62 increased to 45 points, after cycle 2 the average value was 83.3 and an increase of 60 points. Based on the results of the research and discussion, it can be concluded that there is an increase in news listening skills in class X students when using the audiovisual learning model.